Life is elsewhere : symbolic geography in the Russian provinces, 1800-1917 - Lounsbery, Anne (NIU series in Slavic, East European, and Eurasian studies., 2019)
"Author shows how nineteenth-century Russian literature created an imaginary place called "the provinces"--A place at once homogeneous, static, anonymous, and symbolically opposed to Petersburg and Moscow"--